Hr Management in the Digital Era in MSMEs - Agus Dharmanto; Cahyadi Husadha; Novita Wahyu Setyawati; Siti Nur Assyifa (PT FORMOSA CENDEKIA GLOBAL, 2023)
Micro, small and medium enterprises (MSMEs) are the most dominant business category in Indonesia. Most small businesses face challenges when it comes to educating their staff about digital trends and business opportunities. The existing problems can be concluded that the problem is that there are still human resources who do not know the potential and management that exists in them in the face of the digitalization era. Therefore it needs to be encouraged to be directed in knowing the potential and management that exists in him and provide training on how to take solutions when facing a problem.The performance target achieved by community service this time is the aspect of ability, in which existing human resources can improve their skills and ability to solve problems and manage